Pigment cell-specific expression of the tyrosinase gene in ascidians has a different regulatory mechanism from vertebrates. - Toyoda, R; Sato, S; Ikeo, K; Gojobori, T; Numakunai, T; Goding, C; Yamamoto, H (2000)
Tyrosinase is the key enzyme required for the synthesis of melanin pigments. Sequence comparison and functional analysis of the 5' upstream regions of vertebrate tyrosinase genes have revealed the importance of conserved E-box motifs in regulating their specific expression in pigment cells, optic cup-derived retinal pigment epithelium (RPE) and neural crest-derived melanocytes. In ascidians (more basal protochordates), two pigment cells that resemble vertebrate RPE cells are formed and specifically express the orthologous tyrosinase gene (HrTyr) in the cerebral vesicle located at the anterior end of the neural tube. To define regulatory sequences required for pigment cell-lineage-specific expression of HrTyr during embryogenesis, a series of mutations of the 5' upstream region of HrTyr were fused to the lacZ reporter gene and were microinjected into fertilized eggs. We found that the -152bp upstream of the translational start site is essential for expression in pigment cell precursors of tailbud-stage embryos. Further, additional positive and unique restriction elements were identified in the region up to -1.8kb. Surprisingly, in the -152bp minimal promoter or in other regions with regulatory activities, there are no E-box motifs or sequences correlating with other conserved elements regulating vertebrate tyrosinase promoters. The possibility that Pax proteins regulate HrTyr expression is also discussed.